Benefits over risks: A case study of government support of energy development in the Russian North. (June 2019) - Sidortsov, Roman
Abstract: Projected benefits serve as the driving force behind hydrocarbon development. Such benefits are analysed in conjunction with the risks posed by proposed oil and gas activities, leading to an ostensibly rational decision on whether to proceed with the development. This article explores the ways and extent to which government policies aimed at supporting the oil and gas sector affect the outcomes of decision-making processes regarding new hydrocarbon projects. The article is premised upon a case study of the Russian Arctic and Subarctic. The study utilizes transcripts of key presidential meetings and speeches, as well as applicable programmatic policy statements, laws, and administrative regulations. The data is subjected to the complimentary and corroborative discourse and legal analyses. The article concludes that the dominance of benefits over risks in the policy discourse is particularly impactful in the decision-making process regarding new oil and gas development in Russia. Highlights: Discussion of oil and gas development benefits dominates policy discourse in Russia. Benefits are discussed before risks. Disproportional amount of time given to the discussion of benefits. Benefits are generally presented as certain and risk as improbable. Legal mechanisms for governing risk are, therefore, significantly impacted.